Mechanisms of Communication and Meaning Production in Theatrical Discourse - ouile, hamza (El Omda in Linguistics and Discourse Analysis, 2018)
Theatrical discourse is formed from a collection of discourses, the most prominent of which is the author’s discourse, a linguistic discourse created by a playwright and directed toward a reader or spectator. In this, it aligns with any other literary discourse that relies on language as a means of communication. However, a theatrical performance does not convey meaning solely through linguistic signs; it also interacts with other theatrical elements as mechanisms for transmitting signs. The audience engages with these verbal, visual, and kinetic signs, producing, in the end, a meaningful discourse in which the components of theatrical performance—acting, set design, props, costumes, and lighting—intertwine to shape its structure.